Generalized intuitionistic fuzzy interactive geometric interaction operators using Einstein t-norm and t-conorm and their application to decision making. (November 2016) - Garg, Harish
Highlights: A series of generalized Intuitionistic fuzzy Einstein aggregation operators are developed. Interaction between the membership and non-membership has been considered. Shortcoming of the existing functions is overcome. Sensitivity analysis of decision maker preferences has been assessed. A systematic comparison between the existing work and the proposed work have been given. Abstract: The present paper proposes some new geometric aggregation operations on the intuitionistic fuzzy sets (IFSs) environment. Based on it, a new class of generalized geometric interaction averaging aggregation operators using Einstein norms and conorms are developed, which includes the weighted, ordered weighted and hybrid weighted averaging operators. Furthermore, desirable properties corresponding to proposed operators have been stated. Finally, a multi-criteria decision making (MCDM) problem has been illustrated to show the validity and effectiveness of the proposed operators. The computed results have been compared with the existing results.